Shamballa - A short essay on the relationship between the city, the world and the expansion of consciousness. - Davide C. Crimi (Academicus, 2020)
Starting from the images of the myth of the city of Shamballa, this essay intends to examine its sources and above all the power of vision which, by combining different exegetical lines, ends up assuming complete existential indifference with respect to the traditions of extraction. From this change of perspective derives a different vision of reality, a “today” gifted by instantaneous knowledge and simultaneous communication have become realities that prove more advanced than our actual progress in terms of awareness. The city manifests itself in this light in its ontological component, as a breeding ground for souls. This function, so simple and intuitive, is however far from being realized, so much so that we have to declare that we need an intellectual awakening, a liberation from oppression, both of religions and capitalism, that the ecological symptoms make us understand more and more clearly as a condition that can no longer be postponed and for which a spiritual and non-violent struggle must be fought, the only one that can lead to an effective and lasting expansion of consciousness, such as to assume the density, strength and substance of an idea of cosmopolitan, universal citizenship.